Inclusión de las personas con discapacidades sensoriales y físicas en el mercado laboral : el caso de Lima-Perú - Velarde Talleri, Andrés (2015)
The objective of this research is to propose a model of inclusion of people with disabilities (hereby known as PWD) in the labor market of Lima - Peru. Material and Methods: A baseline descriptive, cross-sectional study. Ofthe 10,000 top companies of Peru, 188 companies where chosen aleatory and classified in large 27.1% (51), medium 13.3% (25), Small 48.4% (9) and very small 11% (21). For the quantity information a validated survey was used and for the quality information a narrative matrix was used. Results: Of the universe used, there is only 0.084% of persons with disabilities (PWD) in the payroll of the top companies in Lima. Of the sample, large companies have 0.07%; Medium 0.24%; small 0.21% and 0.69% very small feature in their payroll PWD, whose ages range between 18 and 35 years, although the General Law of Persons with Disabilities says that 3% of the payroll should be PWD. One of the main conclusions is that the companies are not complying with the Law that commands to insert PWD in their payroll, because they are only incorporating an average of 0.084%, far below from the 3% indicated as the standard;however, there is availability to insert PWD according to a profile by company type that requires it.